(3TQM GdebOeI GdCLQhejIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3eMeO SYjO Hf CMeOs)
(3ChdgG (B:s
(3hHYO agPG TQM dWja dCdaGX GdCLQhejI aj CUhd Yde GdYQHjI jfJaY HgG GdeHJOj Ef TGA Gddg JYGdi hdG jMJGL EdjgG GdefJgj YdeJg ddUZGQ aj Gdaf hGdCWaGd dG ddeeGQSjfs
(3BNQgG (B:s
(3heG CTHg Pdc ef CeKdI GdbSejf GdChdjf Chd GdKdGKI hCeG JGHY GdeNahV abO JbOe PcQg aj GdeQahYGJ adjQGLY LejY Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 8 / 26s
(3cTa GdXfhf(B: 2 / 1796s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs